RETRACTED: A Dynamic Analysis of the Asymmetric Effects of the Vocational Education and Training on Economic Growth, Evidence From China - Xia, Linzhong; Ali, Arshad; Wang, Haotian; Wu, Xun; Qian, Dake (Frontiers in Psychology, 2022)
Since 2010, China's economic growth has stagnated due to an unbalanced regional industrial structure and lack of sufficient qualified technical personnel. A nonlinear autoregressive distributed lag (NARDL) model has been used in this study to examine the asymmetric effects of secondary vocational education and training (SVET) and higher vocational education and training (HVET) and their interaction with high-tech industries on economic growth over the period 1980–2020. The findings show that an increase in secondary vocational education and training (SVET) significantly boosts long-term economic growth, while a decrease in secondary vocational education and training (SVET) insignificantly reduces long-term China economic growth. Likewise, the upward change in higher vocational education and training (HVET) promotes and the downward fluctuation in higher vocational education and training (HVET) significantly reduces China's long-term economic growth. The moderating role of secondary vocational education in the impact of high-tech industries on China's economic growth is positive, but not significant. However, higher vocational education plays a significant positive moderating role in high technology industries impact on economic growth. Strategically, the study analysis suggests that economic transition prosperity can be achieved by encouraging higher vocational education and the equal development of high-tech industries in all regions. In addition, this study also proposes to cultivate high-quality talents related to high-tech development and modern industrial innovation and upgrading through higher vocational education, improve productivity, and promote the country's intensive development.